I Don't Want to Go Back: Examining the Return to Physical Workspaces During COVID-19. Issue 11 (November 2020) - Liu, Zihan; Van Egdom, Drake; Flin, Rhona; Spitzmueller, Christiane; Adepoju, Omolola; Krishnamoorti, Ramanan
Abstract : Objective: We study employee perspectives on return to physical workspaces to ultimately inform employers' and policy makers' decision making around the return to work during COVID-19. Methods: We tested the three-component conceptual model using survey data collected in the United States in May 2020 from samples of energy workers ( N  = 333). Results: Women, non-Caucasians, and employees living in multi-generational households were less willing to return. Concerns about childcare were negatively related to willingness to return, whereas organizational strategies for mitigating COVID-19 transmission at work were positively related to willingness to return. COVID-19 infections in an employees' network were also negatively related to employees' willingness to return. Conclusions: Blanket policies may miss the nuanced needs of different employee groups. Employers and policy makers should adopt flexible approaches to ensure a return to workspaces that addresses employee concerns and needs.